Staffing needs and utilization for alternative contracting methods in highway design and construction. Issue 9 (17th April 2020) - Tran, Dai Q.; Harper, Christofer M.; Smadi, Adi M.; Mohamed, Mamdouh
Abstract : Purpose: This research investigates procedures and effective practices on staffing needs and utilization for successful implementation of alternative contracting methods (ACMs) in the United Sates, including design–build (D–B) and construction manager/general contractor (CM/GC) delivery methods. Design/methodology/approach: The review of published empirical studies, a national survey of transportation agencies and case studies of highway agencies form the basis of the conclusions in this research. In addition to the national survey, with 46 of 50 agencies participating, the research presents case studies from five highway agencies in the United States including the following: California, Florida, Georgia, Minnesota and Virginia. These five case studies were selected from agencies that have extensive experience in delivering ACM projects. The case studies involved a thorough procedural review and structured interviews of agency personnel. The agencies then validated the results and conclusions. Findings: The results showed that implementing ACM projects requires different knowledge, skills and management and coordination efforts than traditional design–bid–build (D–B–B) projects. The study found that the key success factors of implementing ACMs are the following: (1) establishment of an ACM champion; (2) active involvement of key staff throughout the ACM project development process; (3) appropriate use of consultants and (4) ACM training and staff development. Research limitations/implications: The issue on how to attract and retain talented staff and a committed core workforce with appropriate skills and competences for ACM implementation is vital for highway agencies, but it lacks information and guidance. The chief limitation of this research is that the primary data were collected from highway agencies in the United Sates. Any future research should include more data to enhance the validity of this study outside of the public transportation sector. Practical implications: Developing a sustainable level of core staff plays an important role in implementing an ACM program. The result of this research will help transportation agencies and other public owners to develop effective staffing strategies for successful implementation of ACMs. The findings of this research also address the appropriate use of consultants to supplement core staff with regard to delivery of ACM projects. Originality/value: This research is the first attempt to examine the staffing needs and utilization for ACM projects.